Parenting Patterns and the Effect on Children's Characteristics - Rhona Sandra; Neviyarni S (Pascasarjana, Universitas Negeri Padang, 2022)
Parents play an important role, especially in the process of growing and developing children, from birth to growing into adults. This is clear evidence that parents can influence children. One of the common pieces of evidence is having a genetic makeup that will influence the behavioral characteristics of children, and also how children are treated by their parents. Twin and adoption studies provide a strong basis for estimating the strength of genetic effects, although the strength of genetic factors is not a sufficient basis for influencing the characteristics of children, because environmental factors also contribute to parenting efforts which are closely related. Children learn to learn many things through everyday experiences in interacting with the physical and social world, but what is learned is not coded in genes. Some of the experiences children have are random, not planned or orchestrated by any outside agency but some occur according to the so-called socialization timetable. This is where parenting comes into play.